Pendidikan Karakter Anak Usia Dini - Heldanita, Heldanita; Suyadi, Suyadi (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
Education of early childhood is the important thing in childrens? self and first container to invest character education. The aim of this research is to know the concept of character education according to Thomas L and Al Ghazali then to know the comparison their thoughts. This research is qualitative with library research. Result shows that Thomas and Al Ghazali are extraordinary people who has given intelligence by God to think problem people don?t think. They both think that world needs human that has good moral and education. The base difference located in how Al Ghazali leant every aspect from character education to Islam meanwhile Thomas leants on experience and researches. The difference of view from these figures is not producing a gap but collaborating to produce a new concept that is spirituality character education.